Kinematic Analysis of 2-Point and 3-Point Jump Shot of Elite Young Male and Female Basketball Players - Vencúrik, Tomas; Knjaz, Damir; Rupčić, Tomislav; Sporiš, Goran; Li, Feng (International journal of environmental research and public health, 2021)
Basketball shooting is one of the most important offensive skills in basketball. Winning or losing a game mostly depends on the shooting effectiveness. The study aims to compare the selected kinematic variables of 2-point (2-pt) and 3-point (3-pt) jump shots (after making a cut and receiving the ball) and ascertain the differences between elite male under 16 and 18 (U16M, U18M) and female under 16 and 18 (U16F, U18F) basketball players. Overall, forty-eight young male and female basketball players participated in the study. 3D motion analysis using an inertial suit with the addition of utilizing a smart ball was performed for assessing the 2-pt and 3-pt shooting techniques. Players in male categories shot for 2-pt with a higher center of mass difference in the vertical direction (U16M 5.7 cm, U18M 3.9 cm vs. U16F 1.4 cm, U18F 0.6 cm), with higher release shoulder angle (U16M 110.9, U18M 113.8 vs. U16F 103, U18F 105), and with a higher entry angle of the ball (U16M 34, U18M 32 vs. U16F 30, U18F 30) when compared to female categories (p < 0.001). In the 3-pt shooting, there were differences between male and female categories in the shoulder angle when releasing the ball (p < 0.001). In the players shooting speed, there were differences between U16M vs. U18F (0.95 ± 0.1 vs. 0.88 ± 0.1; p = 0.03) and U16F vs. U18F (0.96 ± 0.06 vs. 0.88 ± 0.1; p = 0.02) players. Male categories shot 3-pt shots with a smaller center of mass difference in the horizontal direction when compared to 2-pt shots (p < 0.001). The entry angle was higher in successful shooting attempts compared to unsuccessful shooting attempts when shooting for 3-pt (p = 0.02). Player shooting speed was higher in all categories (except U18F) when shooting for 3-pt (p < 0.001). It appears that performers show difference in kinematic variables based on distance from the basket. Basketball coaches and players should work to minimize the kinematic differences between 2-pt and 3-pt shooting and to optimize the shooting technique.
Keywords: rameno; curl cut; pohyb těles; Female; entry angle; Basketball; Motion; biomechanika; ženské pohlaví; catch-and-shoot; mužské pohlaví; Male; center of mass; basketbal; Biomechanical Phenomena; Shoulder; shoulder angle